Penerapan Metode Klasifikasi C4.5 dalam Pembuatan Website Identifikasi untuk Prediksi Kredibilitas Akun pada Media Sosial Instagram - Yonas Christianto; Rolly Intan; Rudy Adipranata (Jurnal Infra, 2021)
Instagram is one of the biggest social media platforms nowadays. As one of the biggest platforms, there’s also a lot of people who makes this platform become unhealthy social media environment, by making fake or spam accounts. This is the problem that the author is trying to solve. By developing a website that people can use to gain information about the credibility of an Instagram account, so users can interact with the target accounts safely and comfortably. The method used to predict the credibility is C4.5 classification which produce decision rules. This decision rules will be used to predict the credibility of an Instagram account. Based on the test that have been carried out, the website can be used to determine the credibility of an Instagram account and the result of the classification method reached to 97,07%.